Effectiveness Of Two Stay Two Stray Learning Techniques In Indonesian Language Learning - Yanuri, Yanuri; Wardiah, Dessy; Ardiansyah, Arif (Jurnal Pendidikan Tambusai, 2021)
This research aims to describe the effectiveness of the Two Stay Two Stray learning techniques in Indonesian at school. This research is a quasi-experimental research. Data collection techniques in this study used test and documentation techniques. The test instrument is given to students with the aim of knowing or measuring knowledge and assessing students' understanding of learning Bahasa Indonesia using the Two Stay Two Stray technique. The analysis technique was carried out in the experimental class and the control class.